Effect of imbalance in dietary macronutrients on blood hemoglobin levels: a cross-sectional study in young underweight Japanese women - Tateishi, Yuko; Ichikawa, Reiko; Suzuki, Katsuya; Kitahara, Yoshiro; Someya, Yuki; Tamura, Yoshifumi (Frontiers in Nutrition, 2023)
Background: Iron deficiency and underweight are common nutritional problems among young Japanese women, many of whom show unhealthy dietary patterns owing to a desire for thinness. We conducted a cross-sectional analysis of the relationship between iron status, nutritional status, and dietary intake among young Japanese women with underweight to identify dietary risk factors for iron deficiency. Methods: Of the 159 young women (18–29 years of age) enrolled, 77 underweight and 37 normal-weight women were included in the study. They were further categorized into four groups based on quartiles of hemoglobin levels among all participants. Dietary nutrient intake was ascertained using a brief self-administered diet history questionnaire. Blood level of hemoglobin and nutritional biomarkers such as total protein, albumin, insulin-like growth factor-1 (IGF-1), and essential amino acids were measured. Results: In underweight, the multiple comparison test showed that dietary intakes of fat, saturated fatty acid, and monosaturated fatty acid were significantly higher and carbohydrate intake was significantly lower in the group with the lowest hemoglobin level, whereas intakes of iron were the same across groups. Multivariate regression coefficients suggested that replacing fat with protein or carbohydrates increased hemoglobin levels under isocaloric conditions. Additionally, significant positive correlations were observed between hemoglobin levels and nutritional biomarkers. Conclusion: Dietary iron intake did not change across different hemoglobin groups among Japanese underweight women. However, our results suggested that an imbalanced dietary macronutrient induces anabolic status and hemoglobin synthesis deterioration among them. Especially, a higher fat intake may be a risk factor for lower hemoglobin.